Habituasi Nilai-Nilai Interaksi Budaya Bumi Alit Kabuyutan Batu Karut pada Mata Pelajaran IPS dalam Penguatan Karakter Abad 21 di SMP Se-Kecamatan Arjasari Kabupaten Bandung - Hasim Bisri; Khaerul Syobar; Neneng Tripuspita (Departement of Mathematics Education, 2024)
This research is motivated by the almost unstoppable impact of globalization, supported by the development of sophisticated internet technology. Globalization affects all aspects of life, bringing significant changes to society both locally and globally. Internet technology, although intended to bring positive benefits and make human work easier, also has negative impacts if not handled wisely. The aim of this research is to explore the values ​​of cultural interaction found in Bumi Alit Kabuyutan Batu Karut, Lebakwangi Village, Arjasari District, Bandung Regency and to implement the research results through a process of habituation of cultural interaction values ​​in social studies subjects in strengthening 21st Century Character education for junior high school students. /equivalent throughout Arjasari District, Bandung Regency. Data collection techniques use interviews, observation. The method used in this research is a qualitative descriptive analysis method. The qualitative descriptive analysis method is a method used to analyze data to produce a final conclusion in solving a problem. The population in this research are students at the junior high school level in Arjasari District, Bandung Regency. The sample is students in class VII at SMPN 1 Arjasari. In qualitative research there is actually no sample but the term informant is used. Informants are determined based on subjective research from researchers (purposive). Informants are selected using the criteria of initial informants (principal) and designated informants (base), with the assumption that the selected informants are considered representative of a homogenous society. Informants as research sources include main informants and base informants. The results of this research show that the social interaction values ​​on this site include: 1. Self-Orientation Values, 2. Religious Interaction Values, 3 Moral Values, 4. Compassion Values, 5. Social Responsibility Values, 6. Social Harmony Values Alive, Overall, this research shows that the Bumi Alit Kabuyutan Lebakwangi-Batukarut Site has important cultural and historical values, but awareness of this culture is starting to erode among the younger generation.